Performance Evaluation of Bio-Inspired Pattern-Based Tensile Specimens for Lightweight Electric Vehicle Battery Applications - Bala Murali Gunji; Ramakrishna Doodi; Mathews Koshy (Engineering Proceedings, 2024)
Currently, researchers are seeking to pay more attention to lightweight designs to minimize the materials used and greatly improve the strength of designs to increase their loading capacity in engineering applications. Bio-inspired patterns are given more attention in the design of these lightweight structures. In this current study, tensile specimens are fabricated as per the ASTM D638-IV standard and through the VAT photopolymerization technique with different bio-inspired patterns like honeycomb, re-entrant, and spider web structures, with unit cell sizes of 4 mm and 6 mm, respectively. Tensile tests are conducted on all the specimens, and all the test results are compared and evaluated to determine the one with the best performance. It was concluded that the 4 mm unit cell size specimens performed well, and spider web structures were shown to have especially satisfactory performance.